Can the cervical length in mid-trimester predict the use of vacuum in vaginal delivery? - Jee Yoon Park; Sun Min Kim; Jeenah Sohn; Sejin Kim; Eunjin Song; Byoung Jae Kim; Hye Won Jeon (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveThis study aimed to evaluate whether an increased cervical length (CL) measured in the mid-trimester is associated with vacuum-assisted vaginal delivery.MethodsThis retrospective cohort study included women who delivered vaginally in Seoul National University Bundang Hospital (n=820) and Boramae Medical Center (n=509) between January 2017 and February 2019. Multifetal pregnancies and preterm births before 37 weeks of gestation were excluded. Only those cases in which CL was measured at 18-22 weeks of gestation for the purpose of screening for preterm birth risk in each institution were analyzed (n=537). Other significant risk factors were reviewed.ResultsThe median gestational age at delivery was 39.4 weeks (range, 37.0-41.6 weeks); 18.6% (100/537) were vacuum-assisted delivery. There was no relationship between mid-trimester CL and vacuum-assisted delivery (odds ratio [OR], 0.96; 95% confidence interval [CI], 0.57-1.62), while nulliparity was associated with a higher risk (OR, 3.64; 95% CI, 1.55-8.57) than multiparity. When the population was divided into 3 groups by CL range, vacuum-assisted delivery rates increased as CL length increased in nulliparous women.ConclusionMid-trimester CL did not predict the need for vacuum-assisted vaginal delivery.